Pataya: Suatu Tinjauan Konstruksi Tempat Ngèbèr Komunitas Gay di Surabaya - Azali, Kathleen (Makara Human Behavior Studies in Asia, 2012)
Tempat ngèbèr, or hanging-out places where gay men in Indonesia meet, can be found in various—though relatively hidden—public places across Indonesia. Tempat ngèbèr as one of the more prominent sites in the constellation of gay serves not only as a space to find sexual partners, but also to socialize, to be open in expressing oneself, and to gain acceptance from one’s peers. Surabaya has a number of famous, well-known tempat ngèbèr, with Pataya being one of the largest places. Yet changes within the last few years have diminished its popularity. Through participant observation and non-formal interviews, this research attempts to understand how Pataya became the more prominent tempat ngèbèr in Surabaya, and what kind of changes have happened that reduced its popularity. Hopefully, this research will bring about future studies that will investigate various adaptations that can be carried out inside or outside the site itself.